Thessalonicensia. Notes on IG X 2.1s (2) - Martín González, Elena; Hallof, Klaus (Tekmeria, 2020)
The present paper constitutes an introduction to the second volume of the supplement to Inscriptiones GraecaeX 2.1, which has just been published. After a brief overview of the history of the epigraphic corpus of Thessaloniki, a description of the structure and content of the new volume is offered, with a focus on the new evidence regarding the provenance of the monuments. In the second part of the paper, each author presents a selection of the new readings and interpretations which the complete revision of Ch. Edson’s edition has provided.